Morphodynamic of a coastal dune field at San Antonio cape, Buenos Aires, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Coastal dunes are recognized in most of the world coasts, but are particularly common on dissipative beach systems, with low beach slopes, allowing the development of extensive areas of sand supply which provides optimal conditions for their development. The relationship between the beach environments and the coastal dunes regulates the dynamic balance in these types of coasts. Sand supply reduction between the beach-dune system commonly enhances erosion processes on beaches and promotes coastline retreat. The purpose of this paper is to characterize the evolution of the aeolian landforms along a field of transgressive coastal dunes at micro and mesoscale, to estimate natural and human induced causes of modification. The models reconstructing the devel- opment of aeolian landforms derived from this study will be useful to predict future trends on the coastal dune field and for setting tools for environmental management. San Antonio cape is a sand barrier spit that has progradated northward during the Holocene, integrating a depositional sedimentary sequence related to a marine transgression after the last maxi- mum sea level about 6000 years ago (Violante et al., 2001). It extends along the shorefront from Punta Rasa to Punta Médanos and is located in the northeast sector of Buenos Aires province, Argentina (Fig. 1). Geomorphological interpretation is developed using field information and aerial photographs of 1964 (Naval Hydrographic Service) because it shows minimum anthropogenic modifications. Landscape evolution is determined comparing photographs of 1956 (Military Geographical Institute), 1964 (Naval Hydrographic Service), and 1991 (Punta Indio air base) and images from Google Earth. The dune field is developed over a beach ridge plain that reaches a maximum height of 2.5 m. The maximum development of this dune field is at the southern sector of the study area, near Punta Médanos, where it reaches 4 km wide. The dune field width decreases northward having a minimum development near Punta Rasa (Fig. 1). Beaches are sandy, dissipative and with low slope. They can be uni or multibarred and between 40 and 200 m width. Dune fields are recognized according to their stability: inactive and active. The first type is composed of complex parabolic and blow- out dunes. The second one develops seaward, has higher sand transport rates and not many species of vascular plants. Eolian landforms in active dune fields are barchan, barchanoid ridges, and foredunes (Table 1). Foredune in San Antonio occupies a strip parallel to the coast of about 20 to 70 m wide. It is 1 to 10 m high, seaward slopes range from 3 to 7º, while continental slope varies from 7 to 18º. Foredune sediments are composed of well to very well sorted fine sand, with unimodal and symmetrical or slightly negative skewness distibutions. Mean grain size varies from 2 to 2.72 Ø, more than 80% of the sediment is transported by saltation (Table 3). Coarser grain size and more poorly sorted distributions are observed in the southward foredune sediments of Punta Médanos, in response to higher wave energy and the presence of a dissipative to intermediate beach profile (Masselin y Short, 1993). Natural dune environments are characterized by incipient (Fig. 2) and transgressive foredunes (Fig. 3, 4). Foredunes are divided in natural and degraded dunes (Table 2), according to their conservation. The last ones are divided into forest (Fig. 5a and b), forest and fragmentated (Fig. 5c) and razed foredunes (Fig 5d). Where the coastline has curvatures or inflections sand deposition increases on the beach, promoting sediment availability for the beach - dune interaction and favoring the generation of transgressive dunes. However, the analysis of the coastline behavior shows that the coast is retrating between Mar de Ajo and Las Toninas at a rate 1.45 m/year during the last 50 years (López, 2010) and consequently the foredune tends to be degraded and stabilized. The urban process that occupied the coast of Cabo San Antonio began in 1935 resulting in a rapid degradation of the coast (Fig. 6). Human degradation of the dune systems was mainly afforestation, beach and dune mining, building of avenues and houses on the seafront, artificial runoff to the sea and surface impermeabilization. By 1984, a substantial change in the coastal system affected 50% of the active coastal foredune (Fig. 6a). It was estimated a tendency of degradation along the coastal dune system of about 650 m/yr (Fig. 6c) from 1935 to 2000. If this trend continues in the future, the coastal dunefield would be completely degraded by 2030. It is demonstrated that the coastal dune stabilization with exotic plants and tree species, as well as the total or partial devastation for housing, sea front buildings, avenues design, piers construction, and beach resorts have increased vulnerability to the coastal erosion.
Keywords: Foredune, Erosion, Coastal hydrodyna- mics, Cabo San Antonio, Argentina.